Genome-wide association analysis for porcine reproductive and respiratory syndrome virus susceptibility traits in two genetic populations of pigs1. (31st May 2019) - Walker, Lianna R; Jobman, Erin E; Sutton, Kylee M; Wittler, J'Nan; Johnson, Rodger K; Ciobanu, Daniel C
Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV ) is an economically important pathogen that continues to threaten swine industry sustainability. The complexity and high genetic diversity of PRRSV has prevented vaccines from conferring adequate protection against disease outbreaks. Genome-wide association analyses of PRRSV experimentally infected pigs representing two genetic lines ( n = 174 to 176) revealed two major genomic regions accounting for 1.2% of the genetic variation in PRRSV-specific antibody level in serum or lung. The major region for serum antibody was mapped to SSC7 near the SLAII complex, which has also been implicated in susceptibility to other swine viral pathogens. Haplotype substitution analysis uncovered potential DQB1 haplotypes associated with divergent effects. A novel major region for lung antibody was mapped to the proximal end of SSC17 with the top SNP overlapping two genes, PRAG1 and LONRF1 . Sequencing LONRF1 uncovered polymorphisms within the coding region that may play a role in regulating PRRSV-specific antibody production in lung tissue following PRRSV infection. These data implicate novel host genomic regions (SSC17) that influence PRRSV-specific immune response as well as a common region (SSC7) potentially involved in susceptibility to multiple viral pathogens.